Comparative efficacy of dietary interventions for glycemic control and pregnancy outcomes in gestational diabetes: a network meta-analysis of randomized controlled trials - Jiaoyang Di; Jingjing Fan; Fangxu Ma (Frontiers in Endocrinology)
BackgroundGestational diabetes mellitus (GDM) poses significant risks to both maternal and fetal health, and effective dietary interventions are critical for managing the condition. This study aimed to evaluate the efficacy of various dietary interventions on glycemic control and adverse pregnancy outcomes in GDM patients through a network meta-analysis.MethodsA systematic review and network meta-analysis of randomized controlled trials (RCTs) were conducted in accordance with PRISMA guidelines. Data were sourced from PubMed, MEDLINE, Embase, Web of Science, and CNKI up to September 3, 2024. The primary outcomes were fasting blood glucose (FBG), 2-hour postprandial blood glucose (2h-PBG), insulin resistance (HOMA-IR), and adverse pregnancy outcomes, including cesarean section, macrosomia, and gestational hypertension. Effect sizes were reported as odds ratios (OR) for dichotomous outcomes and mean differences (MD) or standardized mean differences (SMD) for continuous outcomes, with 95% confidence intervals (CI).ResultsA total of 28 RCTs with 2666 participants were included, evaluating seven distinct dietary interventions. Among them, 19 studies assessed the low-glycemic index (Low-GI) diet, 4 evaluated the Dietary Approaches to Stop Hypertension (DASH) diet, 4 investigated low-carbohydrate diets, 1 examined the low-glycemic load (Low-GL) diet, and 1 explored a combined low-carbohydrate and DASH diet. The remaining trials compared standard dietary recommendations or structured meal planning. The DASH diet was the most effective intervention for glycemic control, significantly reducing FBG (SMD = -2.35, 95% CI [-4.15, -0.54]), 2h-PBG (SMD = -1.41, 95% CI [-2.56, -0.25]), and HOMA-IR (MD = -1.90, 95% CI [-2.44, -1.36]). Both the DASH and Low-GI diets significantly reduced adverse pregnancy outcomes. Specifically, the DASH diet significantly reduced the risk of cesarean section (OR = 0.54, 95% CI [0.40, 0.74]), while the Low-GI diet significantly reduced the risk of macrosomia (OR = 0.12, 95% CI [0.03, 0.51]).ConclusionThis network meta-analysis suggests that the DASH and Low-GI diets may be beneficial for managing gestational diabetes mellitus. The DASH diet showed favorable trends in improving glycemic control, while both diets appeared to reduce the risks of cesarean delivery and macrosomia. Further high-quality research is needed to confirm these findings and optimize dietary recommendations for clinical practice.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/, identifier CRD420251008181.